PENGEMBANGAN USAHA KECIL RENGGINANG EMAK YANG MENGUBAH KEHIDUPAN - Adelia Agustin; Febri Ariyantiningsih; Himayyah Himayyah; Putri Bintang Aprilia Lestari (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The development of the rengginang emmak business presents a strategic opportunity for moicro, small, and medium enterprises (MSMEs) to maintain their existence and increase the competitiveness of local products.Rengginang, a food with significant cultural value and economic potential, faces several challenges including limited marketing, competition from modern products, and changes in consumer behavior. Rengginang Emmak is a small MSME producing traditional Indonesian snack. Founded by a housewife (Siti Yuliatun), she sought to increase her family’s income by utilizing local resources and fresh, high-quality ingredients. Rengginang Emmak has successfully created a delicious and nutritious product. This articel will discuss the development of the rengginang emmak business using the right strategies to ensure that the business can not only survive but also grow sustainably amidst modern food.